EVALUASI PELAKSANAAN PEMBUATAN SUMUR RESAPAN DI KECAMATAN TAMPAN KOTA PEKANBARU (STUDI EVALUASI KEBIJAKAN) - Tarigan, Andre Berlin; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The development growth in Pekanbaru, specially in Subdistrict of Tampan expand atfull speed. This matter is visible from a lot of new building to develop building. But buildingsstanding to lessen the diffusion area irrigate so that when the rains arrive will be able tocause floods. One of way of to overcome this matter is government of Pekanbaru by releasingthe policy about Obligation of Making of Diffusion Well In Each Building Which Stand Up asaccording to the local regulation No. 10 of 2006 about resource irrigate and diffusion welland as duty executor and straightening of the rule of district is Institute of Planology andBuilding of Pekanbaru. This research is done to evaluate the policy of making of diffusionwell.Concept of the theory is that researchers use evaluation. The evaluation consists ofeffectiveness, efficient, sufficiency, responsiveness and accuracy. This research usedqualitative research methods with study of descriptive data. In collecting data, the researcheruse interview techniques, observation and study of literature. By using key informan and theinforman as a supplementary source of information.Based on the findings through observations and interviews, earn in known that theExecution of Policy of Making of Diffusion Well in Subdistrict of Tampan Pekanbaru not yetmaximal. This matter seen from its maximal of socialization, still the lack of SDM in runningpolicy, and still less specifically given sanction.Keyword : Policy, Evaluation, Diffusion Well